Downregulation of Barley Regulator of Telomere Elongation Helicase 1 Alters the Distribution of Meiotic Crossovers - Barakate, Abdellah; Arrieta, Mikel; Macaulay, Malcolm; Vivera, Sebastian; Davidson, Diane; Stephens, Jennifer; Orr, Jamie; Schreiber, Miriam; Ramsay, Luke; Halpin, Claire; Waugh, Robbie (Frontiers in Plant Science, 2021)
Programmed meiotic DNA double-strand breaks, necessary for proper chromosomal segregation and viable gamete formation, are repaired by homologous recombination as crossovers (COs) or non-crossovers (NCOs). The mechanisms regulating the number and distribution of COs are still poorly understood. The REGULATOR OF TELOMERE ELONGATION HELICASE 1 (RTEL1) DNA helicase was previously shown to enforce the number of meiotic COs in Caenorhabditis elegans but its function in plants has been studied only in the vegetative phase. Here, we characterised barley RTEL1 gene structure and expression using RNA-seq data previously obtained from vegetative and reproductive organs and tissues. Using RNAi, we downregulated RTEL1 expression specifically in reproductive tissues and analysed its impact on recombination using a barley 50k iSelect SNP Array. Unlike in C. elegans, in a population segregating for RTEL1 downregulated by RNAi, high resolution genome-wide genetic analysis revealed a significant increase of COs at distal chromosomal regions of barley without a change in their total number. Our data reveal the important role of RTEL1 helicase in plant meiosis and control of recombination.